The Regulations of Financial Conglomerates in Five Asia Countries and Australia: A Policy Comparative Study - Ridhona Fultanegara; Hamzah, Muhammad Zilal; Sofilda, Eleonora (International Journal of Economics, Management and Accounting, 2024)
Financial conglomerates are considered to have a significant role in a country’s economy. A well-developed financial conglomerate will bring economy’s positive growth. However, when one collapses, systemic risk cannot be avoided to the financial system. The study conducts a comparative analysis of financial conglomerates/financial holding companies policies in six countries: Indonesia, South Korea, Taiwan, Malaysia, Singapore, and Australia. Furthermore, the research examines the literature review method of financial conglomerates criteria, structure, synergy, intragroup transactions, and data protection. In general, the requirements of financial conglomerates within research sample countries align with the Joint Forum. Indonesia is still developing the financial conglomerate’s minimum assets and members. Singapore is more concerned with a portion of assets, capital, liabilities, or income, while Taiwan regulates the total assets and paid-in capital. Malaysia regulates strictly with specific minimum ownership, while Australia focuses more on transaction materiality. The synergy among members of financial conglomerates may improve efficiency—however, the intragroup transactions raise systemic risk. Consumer data protection should be considered when financial conglomerates conduct cross-selling. From this study, policymakers should enhance their policies so that financial conglomerates take more advantage of generating the country’s economy while managing challenges to the financial system’s stability.